2016
DOI: 10.3389/fpsyg.2015.02029
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Recall of Words Spoken in Their First and Second Language: Effects of Signal-to-Noise Ratio and Reverberation Time

Abstract: Speech perception runs smoothly and automatically when there is silence in the background, but when the speech signal is degraded by background noise or by reverberation, effortful cognitive processing is needed to compensate for the signal distortion. Previous research has typically investigated the effects of signal-to-noise ratio (SNR) and reverberation time in isolation, whilst few have looked at their interaction. In this study, we probed how reverberation time and SNR influence recall of words presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
3
19
0
1
Order By: Relevance
“…Thus, the pupils who were good at reading English benefited significantly from a short reverberation time, while those who were not so good at reading English gained more benefit from a long reverberation time. Besides our previous research [ 5 – 6 ], we have not encountered any other research that has found an enhancement effect on recall or speech comprehension from a long reverberation time. All previous research on the effects of reverberation on recall and speech comprehension has only shown detrimental effects.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the pupils who were good at reading English benefited significantly from a short reverberation time, while those who were not so good at reading English gained more benefit from a long reverberation time. Besides our previous research [ 5 – 6 ], we have not encountered any other research that has found an enhancement effect on recall or speech comprehension from a long reverberation time. All previous research on the effects of reverberation on recall and speech comprehension has only shown detrimental effects.…”
Section: Resultsmentioning
confidence: 90%
“…However, there is a possibility that reverberation not always has a detrimental effect. We have previously found in our research that a long reverberation time can improve recall for words spoken in English and Swedish when compared with a short reverberation time, at least when the signal-to-noise ratio is low [ 5 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under environmental conditions in which the sound signal is degraded or distorted, a number of past experiments have shown that greater demands are placed on mediating cognitive processes. For example, poor acoustic conditions such as long RT and additional background noise have been shown to impair listening comprehension (Klatte, Lachmann, & Meis, 2010;Peng & Wang, 2016;Sörqvist, Hurtig, Ljung, & Rönnberg, 2014), memory of spoken words (Hurtig et al, 2016;, memory of spoken lectures (Ljung, Sörqvist, Kjellberg, & Green, 2009) and learning (Hygge, 2003;Hygge, Evans, & Bullinger, 2002). Therefore, acoustic conditions in environments in which education takes place should provide the highest quality acoustics as speech perception is such an important aspect of education.…”
Section: Reverberation Time and Second Language Listening Comprehensionmentioning
confidence: 99%
“…However, the value of the acoustic environment for learning is underestimated in Sweden, as a consideration of the Board of Director's regulations, BBR (Boverkets Byggregler), for classroom environments indicate. As the BBR states that sound classroom environments must be in accordance with Swedish standards (SS25268: 2007), RT in a Swedish classroom must be in the range of 0.5-0.8 s as per specifications for buildings in sound Class C. It is unclear what motivates the BBR's choice of RT for Class C sound environments, but how speech perception is negatively affected as a function of increased RT has been considered in a number of studies (Hurtig et al, 2016;Klatte et al, 2010;Klatte, Bergstroem, & Lachmann, 2013;Ljung, 2010;Nábělek & Donahue, 1984;Sörqvist et al, 2014).…”
Section: Reverberation Time and Second Language Listening Comprehensionmentioning
confidence: 99%
“…Innerhalb der analysierten Literatur wurde in den beiden Arbeiten von Madbouley und Kollegen [27] [16,23]. Fazit dieser Studien ist somit, dass in Fällen, in denen die Sprachwahrnehmung (durch persönliche oder umweltbedinge Faktoren) beeinträchtigt ist, eine geringfügig längere Präsentationsdauer dazu führen kann, dass Worte leichter verstanden und besser erinnert werden können [16,23].…”
Section: Ganzheitliche Modelle Zur Bewertung Von Klassenraumakustikunclassified